2002
DOI: 10.1557/jmr.2002.0365
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gamma radiation on poly(methyl methacrylate)/single-wall nanotube composites

Abstract: Single-wall carbon nanotube (SWNT)/poly(methyl methacrylate) (PMMA) composites were fabricated and exposed to ionizing radiation for a total dose of 5.9 Mrads. Neat nanotube paper and pure PMMA were also exposed for comparison, and nonirradiated samples served as controls. A concentration of 0.26 wt% SWNT increased the glass transition temperature (Tg), the Vickers hardness number, and modulus of the matrix. Irradiation of the composite did not significantly change the Tg, the Vickers hardness number, or the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…[28] The experimental data published for polymer/SWNT composites [23,24,29,30] demonstrate an increase in permittivity for the composite samples compared with the neat samples. Permittivity data obtained in this study agrees with previously published results.…”
Section: Full Papermentioning
confidence: 99%
See 1 more Smart Citation
“…[28] The experimental data published for polymer/SWNT composites [23,24,29,30] demonstrate an increase in permittivity for the composite samples compared with the neat samples. Permittivity data obtained in this study agrees with previously published results.…”
Section: Full Papermentioning
confidence: 99%
“…The permittivity of the non-transparent melt-blended PMMA±SWNT composite with CNT loading identical to that of the film samples also increased as compared to the neat PMMA. [23,24] Both the electronic nature of the polymer and the effect of CNTs in the composites can be understood by correlating the dielectric constant values from DEA with the refractive index. According to van Krevelan, [31] if the sample is a non-polar insulator, the dielectric constant (e¢) for low frequencies can be expressed by Maxwell's equation e¢ = n 2 ,where n is the refractive index.…”
Section: Full Papermentioning
confidence: 99%
“…It was demonstrated that, in addition to radiation resistance, composite materials had higher mechanical strength and thermal stability, compared with a polymer without fillers 16,[41][42][43][44][45][46] . Relatively small amount of nanofiller is enough for improving properties of CNT-based polymer composites, which are featured by exceptionally high values of elastic modulus and tensile strength (of up to 1 TPa and tens or hundreds GPa respectively), and also thermal and electrical conductivity and high in-air oxidation resistance (>700 o C), without losing their elasticity 44,47,48 .…”
Section: Radiation-resistant and Radiation-shielding Composite Materialsmentioning
confidence: 99%
“…CNTs have been introduced to polyimide films (Delozier et al 2004;Qu et al 2004;Smith et al 2004aSmith et al , b, 2005Watson et al 2005) in order to dissipate any electrostatic charge accumulated during handling or in the charged orbital environment. They have been also dispersed in poly(methyl methacrylate) (PMMA) matrices Muisener et al 2002). It was found that they reduce the degradation of mechanical properties from exposure to g-radiation.…”
Section: Benefits and Challenges Of Aerospace Nanocomposites Related mentioning
confidence: 99%
“…It was suggested that the p-conjugated CNTs acted as radiation sinks, able to effectively dissipate the energy deposited by ionizing radiation Muisener et al 2002;Tatro et al 2004). Najafi et al ) observed a strong protective effect against UV treatment and EBirradiation, due to the effective dispersion and dissipation of the deposited energy by the conductive nanotube network and a strong interaction of the CNTs with the radical species produced in the degradation processes.…”
Section: Benefits and Challenges Of Aerospace Nanocomposites Related mentioning
confidence: 99%